Beyond Neoliberalism: The Role of Community in the Responsibilization of Citizen-Consumers During the Great Recession - Prothero, Andrea; Claudy, Marius; Keating, Andrew (Journal of Consumer Research, 2026)
Drawing on governmentality theory, we examine the formation of responsibilized citizen consumers during Ireland’s Great Recession (2008–2013). Through qualitative analysis of consumer interviews, media and political discourses, and macro consumer data, we advance understanding in governmentality and consumer responsibilization research by theorizing communal responsibilization as a distinct, culturally embedded process. We contrast neoliberal and communal moral frames in responsibilizing citizen consumers, and in this process of “shared responsibility,” we show how many citizen consumers faced ideological, economic, and structural barriers to acting as self-reliant subjects. We find that communal frames and myths were particularly effective in alleviating some of these tensions by fostering relational interdependencies and communal solidarity, thus enabling the moral internalization of responsibility among citizen consumers, both for themselves and others. We identify key mechanisms through which communities facilitated responsibilization and a recasting of citizen consumer subjectivities: social scaffolding, informal resource exchange, active citizenship, and communal entrepreneurship. Finally, we identify tensions and community disintegration as key barriers in the communal responsibilization process. Overall, our findings advance consumer research on responsibilization, consumption communities, and mythmaking.